1 - Guerriers et marchands : éléments pour une économie politique des conflits en Afrique: 10.4314/ad.v24i3.22124 - Hakim Ben Hammouda (Africa Development, 1999)
This article focusses on the study of the new forms of conflict in Africa and their determinants — the new intra-state conflicts which have replaced the Cold-War induced conflicts. The new conflict situations in some countries have become a means for the dominance of politics of closure, a closure of spaces and a hindrance to political transition processes and mechanisms.